Years of life potentially lost in traffic accident victims - Román-Lazarte, Víctor (2022)
Objective: To evaluate the trend and the years of life potentially lost in deaths due to traffic accidents in the department of Tacna. Material and methods: Observational study based on secondary data from the National System of Deaths of the Ministry of Health. A descriptive analysis of the general characteristics of the total number of deaths during the 2017-2021 period was carried out. Years of life lost were also calculated using the formula provided by the Global Burden of Disease. Results: A total of 245 deaths were obtained in the study period, the mean age was 42.98 years with a standard deviation of 19.58. 78 % of the victims were male. More than 80 % were reported in the province of Tacna. In 2020 there was a clear reduction in the number of deaths from traffic accidents. The years potentially lost in the study period were 12 012 years in total, with a large loss in the age group of 20 to 49 years. Conclusion: Compared to other cities in the department of Tacna, there are few deaths from traffic accidents, however, it is important to mention that the young and adult population has a higher proportion compared to other age groups and that these have a greater number of years of life potentially lost. Emphasis must be placed on the promotion and prevention of road safety, and in this way avoid deaths and serious injuries that can lead to disability.